Prenatal visualization of the fetal uterus in routine 2D ultrasound examination - Pedro Azumendi; Marisa Borenstein; Jesús Salvador Jiménez; Ernesto González-Mesa; Carlos Corrales; Guillermo Azumendi; Ignacio Alonso-Usabiaga; Juan Gómez-Salgado; Francisco Javier Fernández-Carrasco (Annals of Medicine)
Objective To establish a new technique to easily identify the fetal cervix-uterus complex in normal female fetuses from 20 to 40 weeks of gestation.Material and methods The study was performed in routine examination in normal fetuses by two observers. Twenty-five consecutive cases per gestational week were assessed between 20 and 40 weeks. The same plane of the bladder used in the assessment of the umbilical arteries was used. In this transverse view of the fetal pelvis different structures can be identified from front to back: the bladder, the bowel and the vertebral body. If the uterus is present, it can be seen between the bladder and the rectum, as a round structure pushing the posterior bladder wall. The echogenicity changes as the uterus develops and increases its size. Voluson E10 ultrasound device (GEHealthcare Ultrasound®, Zipf, Austria) equipped with an RM6Cprobe was utilized.Results Successful identification of the cervix-uterus complex was possible overall in 83.4% of cases, reaching more than 93% from 31 weeks onwards. There was a rapid growth of the cervix-uterus complex after 26 weeks, and in the third trimester appears as a solid round structure behind the fetal bladder. Reproducibility analysis showed agreement between 2 observers in 92% of cases.Conclusion Identification of the uterus and cervix complex is possible from 20 weeks, although it is easier at the end of gestation. This reproducible technique allows the anatomical study of normal female fetuses and the visualization of kidney malformations and disorders of sexual development.